Altered elimination of organic anions in rats with chornic renal failure - Torres, Adriana Mónica (2005)
The progress of chronic renal failure (CRF) is characterized by the development of glomerular and tubular lesions. However, little is known about the expression of organic anions renal transporters. The objective of this work was to study, in rats with experimental CRF (5/6 nephrectomy), the expression of the organic anion transporter 1 (OAT1) and organic anion transporter 3 (OAT3) and their contribution to the pharmacokinetics and renal excretion of p-aminohippurate (PAH). Two groups of animals were used: Sham and CRF. Six months after surgery, systolic blood pressure and plasma creatinine concentrations were significantly higher in CRF groups. CRF rats showed a diminution in: the filtered, secreted and excreted load of PAH; the systemic clearance of PAH; the renal OAT1 expression; and the renal Na-K-ATPase activity. No remarkable modifications were observed in the OAT3 expression from CRF kidneys. The diminution in the systemic depuration and renal excretion of PAH may be explained by the decrease in its filtered and secreted load. The lower OAT1 expression in remnant renal mass of CRF rats or/and the lower activity of Na-K-ATPase might justify, at least in part, the diminished secreted load of this organic anion.